Trophic State of t Tanjung Putus Lake, Kampar District, Riau Based on Trophic Index (TRIX) - Christin M. Saragih; Asmika H. Simarmata; Tengku Dahril (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractMany activities in Tanjung Putus Lake contributes the input of organic and an-organic matter that influence the water quality, especially nutrient concentration in the waters. A research aims to understand the trophic state of the Tanjung Putus Lake’s water based on Vollenweider’s Trophic Index (TRIX), was conducted on March-April 2018. There were 3 stations namely Station 1 (inlet area), Station 2 (the middle of the lake), and Station 3 (outlet area). In each station, there were 2 sampling sites, in the surface and in the middle of water column. Sampling was done three times, once a week. Water quality parameters measured were total posphorus, DIN (Dissolved Inorganic Nitrogen), chlorophyll-a, oxygen saturation, temperature, transparency and pH. Results shown that the total phosphorus: 0.10– 0.14 mg/L, DIN: 0.10 – 0.12 mg/L, chlorophyll-a: 6.41 – 8.50 mg/m3, oxygen saturation: 54.52 – 87.06%, temperature: 30.00 – 32.33°C, transparency: 85.17 – 96.50 cm, pH: 5, and          TRIX: 3.52 – 5.75. Based on the TRIX index value, the water of the Tanjung Putus Lake can be categorized as mesotrophic to eutrophic. Keywords : Water Quality, Oxbow Lake, Mesotrophic, Eutrophic